دور التنمية السياحة في التنمية الاقتصادية المحلية في الجزائر خلال الفترة (2015-2020) - ســعاد أحمد; طـــالبي محمد (جامعة الوادي University of Eloued, 2024)
هدف دراستنا إلى معرفة دور التنمية السياحية في التنمية الاقتصادية المحلية في الجزائر خلال الفترة (2015-2020)، وسبل ترقيتها من أجل مساهمة فعالة، وتم التطرق إلى المقومات و المعوقات السياحية، وقمنا بتحليل بعض المؤشرات الاقتصادية السياحية التي لها علاقة بالتنمية الاقتصادية المحلية. و توصلنا من خلال الدراسة أن مساهمة التنمية السياحية في التنمية الاقتصادية المحلية ضعيفة، و لا ترقى إلى المستوى المأمول، مقارنة بحجم عناصر الجذب السياحية المتاحة والإمكانيات المسخرة.Our study aims to know the role of tourism development in local economic development in Algeria during the period (2015-2020), and ways to promote it for an effective contribution. The components and obstacles of tourism were discussed, and we analyzed some tourism economic indicators that are related to local economic development. Through the study, we concluded that the contribution of tourism development to local economic development is weak and does not live up to the expected level, compared to the size of the available tourist attractions and the capabilities harnessed.
The role of tourism development in local economic development in Algeria during the period (2015-2020)
Keywords: :Local economic development; tourism development; tourism sector; tourism